2019
DOI: 10.1097/aud.0000000000000717
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Variability in Individual Response to Hearing Aid Signal Processing in Wearable Hearing Aids

Abstract: Objectives. Previous work has suggested that individual characteristics, including amount of hearing loss, age, and working memory ability, may affect response to hearing aid signal processing. The present study aims to extend work using metrics to quantify cumulative signal modifications under simulated conditions to real hearing aids worn in everyday listening environments. Specifically, the goal was to determine whether individual factors such as working memory, age, and degree of hearing loss play a role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 60 publications
4
29
0
Order By: Relevance
“…Overall, the participants of the present study would be candidates for hearing aids. Hearing-aid users often show a large variability in terms of benefit and preference to specific forms of hearing-aid processing (Neher et al 2016; Picou et al 2015; Souza et al 2019). In some studies, the HI listeners were stratified based on their audiograms (Gatehouse et al 2006; Keidser et al 1995; Keidser and Grant 2001; Larson et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the participants of the present study would be candidates for hearing aids. Hearing-aid users often show a large variability in terms of benefit and preference to specific forms of hearing-aid processing (Neher et al 2016; Picou et al 2015; Souza et al 2019). In some studies, the HI listeners were stratified based on their audiograms (Gatehouse et al 2006; Keidser et al 1995; Keidser and Grant 2001; Larson et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…al., 2016; Picou et al, 2015; Smeds et 599 al., 2006;Souza et al, 2019). In some studies, the HI listeners were stratified based on their 600 audiograms(Gatehouse et al, 2006; Keidser et al, 1995; Keidser & Grant, 2001; Larson 601 et al, 2002).…”
mentioning
confidence: 99%
“…Individuals with a hearing loss suffer not only from reduced audibility but also from suprathreshold hearing deficits such as impaired binaural, spectral, and temporal processing ( Houtgast & Festen, 2008 ; Johannesen et al., 2016 ; Plomp, 1978 ; Santurette & Dau, 2007 ; Strelcyk & Dau, 2009 ). A number of studies have reported associations between temporal processing abilities and aided speech-in-noise performance ( Lopez-Poveda et al., 2017 ; Souza et al., 2019 ), preference for different compression settings ( Moore & Sęk, 2016 ), or prefitting hearing outcome ( Perez et al., 2014 ). Moreover, binaural hearing abilities have been linked to benefit from different beamforming schemes ( Neher et al., 2017 ).…”
mentioning
confidence: 99%
“…Full details regarding the clinical trial design can be found in Souza et al (2018). Briefly, this trial was a double-blinded randomized crossover design.…”
Section: Methodsmentioning
confidence: 99%